Functionality and quality of life in Brazilian patients 6 months post-stroke - Oliveira-Kumakura, Ana Railka de Souza; Batista, Larissa Mariana Oliveira Santos; Spagnol, Gabriela Salim; Valler, Lenise (Frontiers in Neurology, 2023)
Background: Surviving a stroke poses a social and economic impact that requires the care system to be reformulated and the patient to be addressed in a comprehensive approach. Purpose: This study aims to investigate if there is a relationship between functional activities performed before the stroke, patients' clinical and hospitalization data, and functionality and quality of life measures in the first six months after the stroke. Methods: This study used a prospective cohort of 92 patients. We investigated sociodemographic and clinical data, the modified Rankin Scale (mRS), and the Frenchay Activities Index (FAI) during hospitalization. The Barthel Index (BI) and EuroQol-5D (EQ-5D) were applied at the following time points: 30 days (T1), 90 days (T2), and 180 days (T3) following postictal state. Statistical analysis was conducted using Spearman's coefficient, Friedman’s nonparametric test, and multiple linear regression models. Results: No correlation was found between FAI, BI, and EQ-5D average scores. Severe patients, patients with comorbidities, and patients with extended hospital stays showed lower BI and EQ-5D scores in the follow-up. BI and EQ-5D scores increased. Conclusion: This research found no relationship between activities performed before the stroke and functionalities and quality of life after the stroke, but comorbidities and extended hospital stay were associated with worse outcomes. Implications for nursing practice: Identifying specific needs may guide care planning and optimize rehabilitation.